ANALISIS PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP PRODUKTIFITAS KERJA (Studi Pada PT Kurnia Jati Utama Indonesia - Semarang) - Isnan Hadiyanto, 0835020731; Yunianto, Askar (Students Journal of Economic and Management, 2012)
The research objective was to test and analyze the influence of leadership on labor productivity, test and analyze the influence of environment on labor productivity, test and analyze the effect of compensation on work productivity of employees at PT Kurnia Jati Utama Indonesia â Semarang. in this study population was all employees at PT Kurnia jati Utama Indonesia - Semarang. The sampling technique used in this study is the sampling technique using probability sampling (sampling with equal opportunity for members of the population to be sampled). Probability sampling method used is random sampling. Based on the results of model calculations obtained summary magnitude of adjusted R2 is 0.489 this means that 48.9% variation in labor productivity can be explained by the variation of the three independent variables, namely leadership, work environment and compensation. Based on the results of multiple regression analysis can be seen that the leadership has a positive effect on labor productivity. These effects are statistically significant at 0.011 probability (sig / p <0.05). Work Environment Work positive effect on productivity. Are statistically significant influence on the probability obtained is smaller than Î± of 5% (0.000 <0.05). compensating positive effect on labor productivity. Are statistically significant influence on the probability obtained is smaller than Î± of 5% (0.009 <0.05). It is identified that all the hypothesis is accepted or proven. Key words : leadership, job environment, compensation, and employe productivity